Die vakwetenskaplike en wysgerige betekenis van Stoker se konfrontasie met die ‘moderne desendensieleer’ - Strauss, D. F. M. (Koers, 1994)
In 1926 Stoker wrote an article dealing with the modern biological theory of descent. This contribution endeavours to investigate those arguments and insights which are still valid today. With reference to Von Uexkiill Stoker first of all correctly emphasizes that the Darwinistic theory of descent does not belong within the domain of biology as a special science - it is nothing but a part of philosophy that should be treated within a philosophy of nature. In various contexts Stoker also points out that similarities also presuppose differences something consistently overlooked by Darwinism. The shortcomings in the ‘biogenetic basic law' of Haeckel - which claims that ontogenesis is a recapitulation of phylogenesis as well as of the neglected issue of constancy are lifted out. Stoker in fa d advances a remarkably balanced perspective on the relationship between constancy and dynamics.